ANALYSIS OF THE LEVEL OF SUITABILITY OF SERVICE QUALITY DIMENSIONS FOR PASSENGER SATISFACTION ON GARUDA INDONESIA AIRLINE MAKASSAR – JAKARTA ROUTE - Abd Rahman Kadir; Muhammad Sobarsyah; Dian Viany S. Aritonang (Journal of Risk and Uncertainty Issues, 2023)
Garuda Indonesia is currently included in the 24 airlines in the world for the category four stars (four stars airlines). For the initial steps of priority Garuda Indonesia is reorganized operations and management of Garuda flights to be on time with excellent service quality. As part of the service improvement program, Garuda charted 28 service touch points, ranging from pre to post-journey journeys for passenger comfort. The 28 touch points will be analyzed in this study. This study aims to analyze the suitability of the dimensions of quality services to the satisfaction of Garuda Indonesia airline passenger route Makassar - Jakarta, as well as analyze the quality dimension of the Garuda service to give satisfaction to passengers Garuda route Makassar - Jakarta. Analytical methods used are Level Conformity and Cartesian Diagrams. The results showed that: 1) Garuda service quality dimensions have not been able to give satisfaction to the passenger routes Garuda Indonesia Makassar - Jakarta, 2) Among the five Garuda service quality dimensions, the tangible dimension that has the greatest fitness levels of passenger satisfaction levels Garuda route Makassar - Jakarta.